2016
DOI: 10.1155/2016/1549063
|View full text |Cite
|
Sign up to set email alerts
|

Serum Galectin and Renal Dysfunction in ST-Segment Elevation Myocardial Infarction

Abstract: This study aimed to evaluate the association between serum galectin levels and renal dysfunction in relation to in-hospital prognosis and unfavorable prognosis 1 year after ST-elevated myocardial infarction (STEMI). Patients were assigned to two groups according to the cystatin C-based estimate of GFR on day 12 after STEMI: (1) STEMI patients with normal renal function (GFR based on cystatin C levels = 60 mL/min/1.73 m2) and (2) those with renal dysfunction (RD) (GFR based on cystatin C levels <60 mL/min/1.73 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
(19 reference statements)
1
3
0
Order By: Relevance
“…23 Thus, elevated plasma glucose would both reflect the acute stress and predict an increased propensity for long-term cardiovascular events. 10 Several studies showed that an elevated admission blood glucose in myocardial infarction correlates with an increased incidence of congestive heart failure, cardiogenic shock, and inhospital mortality, [7][8][9][10][11][19][20][21][22] which support our findings.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…23 Thus, elevated plasma glucose would both reflect the acute stress and predict an increased propensity for long-term cardiovascular events. 10 Several studies showed that an elevated admission blood glucose in myocardial infarction correlates with an increased incidence of congestive heart failure, cardiogenic shock, and inhospital mortality, [7][8][9][10][11][19][20][21][22] which support our findings.…”
Section: Discussionsupporting
confidence: 87%
“…Surprisingly, hyperglycemia, as determined by using a simple, low-cost laboratory test, has been associated with a worse prognosis in MI patients, even in the absence of diabetes. 7,8 Patients either with or without a prior history of diabetes mellitus may present with hyperglycemia during acute myocardial infarction. Among patients with no prior history of diabetes, hyperglycemia may reflect previously undiagnosed diabetes, preexisting carbohydrate intolerance, stressrelated carbohydrate intolerance, or a combination of these.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Galectin is a novel target associated with unfavorable prognosis in patients with heart failure. Elevated galectin levels are related to heart failure, and may be a primary regulator of cardiac remodeling with myocardial fibrosis ( 13 ). Galectin-7, as a member of galectin family, plays a role in various events related to the development of the pluristratified epithelium ( 14 ).…”
Section: Introductionmentioning
confidence: 99%